TA`TSIRU MAHARAT AL-LUGHAH AL-‘ARABIIYAH FII INJAAZI HIFDZI AL-QUR’AN LITHALIBAH AS-SHAFI AL-HAADII ‘ASYAR MIN AL-MADRASAH UMMUL QURO AL-ISLAMI BOGOR LIL ‘AM AD-DIRAASII 2020/2021 - Muhammad Firnanda; Emnis Anwar (SHAWTUL ARAB, 2021)
This study aims to examine the strength of the relationship between mastering the Arabic language lessons in the ability to memorize the Qur’an and the importance of the relationship between the ability to learn the Arabic language and the ability to memorize the Qur’an in the eleventh grade of secondary school students. Alia Islamic Boarding School, memorizing the Holy Qur’an, Umm Al-Qur’an, in the academic year 2020/2021. This research is a field research, while the methodology of this research is a quantitative approach, that is, the objectivity of the research design is done by using statistical processing numbers, structures, and controlled experiments. Judging by the population and sample, this study is a population study, as it includes all research topics, namely. The data collection technique used documenting the distribution of the questionnaire. The obtained data were analyzed using quantitative statistics. Arabic language skills for students of the Al-Alia Islamic boarding school for memorizing the Qur’an for the eleventh grade at the Institute for Memorizing the Qur’an, Umm Al-Qura, in the academic year 2020/2021. In a very good category. This can be seen by analyzing the ability of students of the Al-Alia Islamic Boarding School at the Quran Memorization Institute - Umm Al-Qura in the academic year 2020/2021 to memorize in a good category. In this case it can also be seen from the analysis. Based on the spread of the elevator that the researcher made on the quantitative correlative analysis of the results of the study, it was found that there is an effect between the ability of the Arabic language on the ability to memorize the Qur’an for the students of the Al-Alia Islamic Boarding School for the eleventh grade at the Qur’an Memorization Institute, Umm Al-Qura, in the academic year 2020/2021. The results of this study are expected to contribute to the knowledge of teachers, students, parents, schools and other researchers that the level of Arabic language proficiency can affect the memorization of the Qur’an